Software requirements prioritization tool using a hybrid technique - Din, Jamilah; Michael, Ilori; Jasser, Muhammed Basheer (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
Requirements Prioritization (RP) helps to discover the most desired requirements. System developers are not always fully able to implement stakeholders' requirements when time, scope and cost are limited. To solve this challenge, requirements must be prioritized. A fewprioritization techniques have been proposed but nonehasbeen automated. Furthermore, rank reversals (updating rank status whenever requirements are added or deleted) is a major limitation of existing techniques.This paper usesAHP and Cost-Value methodsfor requirement prioritization while addressing rank reversal. The techniques are able to rank every requirement basedon relative value and implementation cost. The AHP method allows an input from the system developers and system users andmakesa pair wisecomparison. The Cost value method ranks the requirements in terms ofthe ratio of value to cost. As requirements increases, human inconsistency in judgment increases.AHP calculates inconsistency and if it is less than 0.1 then stakeholdersshould consider new input values. The prioritization methods are implemented into a prioritization tool which creates a list of the prioritized requirements as output, then consequently generates a scatter plot to display relative values and implementation costs of input requirements.This tool isevaluated in terms ofefficiency (total time taken for prioritization) and ease of use.